2016
DOI: 10.1016/j.psychres.2016.01.048
|View full text |Cite
|
Sign up to set email alerts
|

Young people's difficulty in talking to others about mental health problems: An analysis of time trends in Switzerland

Abstract: The article aimed to analyse time trends regarding young people's willingness to talk about mental health problems. Data on 16774 participants (16-to 20-year olds) of the 'Swiss Multicentre Adolescent Survey on Health' (SMASH) were analysed. The survey was conducted in 1992/93 and in 2002.Logistic regression analyses were conducted to identify predictors associated with the self-reported willingness of youth to talk about mental health problems with adults (other than parents), friends or no one. Socio-demogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…They also feel uncertain about where to find care for their existential concerns in relation to their mental well‐being . However, when seeking care, young adults are willing to talk about their existential concerns . Young adults are aware of their responsibilities regarding their health and well‐being, but they need individualised support and information to make good choices .…”
Section: Introductionmentioning
confidence: 99%
“…They also feel uncertain about where to find care for their existential concerns in relation to their mental well‐being . However, when seeking care, young adults are willing to talk about their existential concerns . Young adults are aware of their responsibilities regarding their health and well‐being, but they need individualised support and information to make good choices .…”
Section: Introductionmentioning
confidence: 99%
“…Anecdotally, some caregivers reported that they felt seeking psychotherapy for young children has become more acceptable and less stigmatizing than seeking psychotherapy for adults in their communities. Empirical evidence indicates that stigma regarding mental health services in general is decreasing in America (Dey, Reavley, & Jorm, 2016; Mojtabai, 2007). We encourage further qualitative and quantitative studies to examine longitudinally changes in stigma.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, new research makes a point that young people, in general, have a hard time talking about their mental health issues to someone else, which contributes to the ongoing problem: people, especially teenagers, not seeking help from others. It also emphasizes how, even when choosing to talk, teenagers prefer informal conversation with peers rather than formal conversation with professionals (Dey et al, 2016).…”
Section: Mental Healthmentioning
confidence: 99%